2020
DOI: 10.1590/0103-6440202002519
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Smoking And Low-Level Laser Irradiation in RANK/RANKL/OPG Expression

Abstract: The objective of this study was to investigate the effects of low-level laser therapy (LLLT) and cigarette smoke on alveolar socket osteoclastogenesis signaling after tooth extraction, in rats. Sixty male Wistar rats were randomly assigned to four groups with 15 animals each: Control Group (with right maxillary molar extraction - ME), Experimental I (with ME and LLLT), Experimental II (with ME and cigarette smoke) and Experimental III group (with ME, LLLT and cigarette smoke). Euthanasia was performed at 3, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Multivariate regression models also showed that cigarette smoking might influence the change of sRANKL in the course of the study. It has been shown that smoking can induce the expression of RANKL mRNA [ 67 ] and increases the sRANKL/OPG ratio by promoting inflammatory cytokines [ 68 ]. In a large case–control study it was demonstrated that cigarette smoking increased the risk for BC in g BRCA1/2 mutation carriers [ 69 ] for which sRANKL/OPG system might present a molecular mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate regression models also showed that cigarette smoking might influence the change of sRANKL in the course of the study. It has been shown that smoking can induce the expression of RANKL mRNA [ 67 ] and increases the sRANKL/OPG ratio by promoting inflammatory cytokines [ 68 ]. In a large case–control study it was demonstrated that cigarette smoking increased the risk for BC in g BRCA1/2 mutation carriers [ 69 ] for which sRANKL/OPG system might present a molecular mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of Kim and colleagues, the effect is dose-dependent—at low concentrations, nicotine appears to have a stimulating effect on osteoblast proliferation, whereas at higher concentrations, the effect is inhibitory [ 43 ]. Cigarette smoke also exerts a direct effect on bone by altering bone-related factors involved in the regulation of osteoclastogenesis, such as the receptor activator of nuclear factor kappa-B ligand (RANKL)/receptor activator of nuclear factor kappa-B (RANK)/osteoprotegerin (OPG) system [ 44 , 45 , 46 ]. RANKL, released by osteoblasts, binds its receptor located on the surface of osteoclast precursor cells, promoting their differentiation and triggering bone resorption, whereas OPG, also released by osteoblasts, interacts with RANK, preventing the binding with its ligand and inhibiting the activity and proliferation of osteoclasts [ 47 ].…”
Section: Pathophysiological Mechanisms Of Smoking Effects On Bone Tissuementioning
confidence: 99%
“…The dental alveolus was curetted and abundantly irrigated, aiming for removal of residual fragments of hard and soft tissues that could interfere with healing. The molar was extracted in each rat with a dental explorer adapted to rat molars with a gentle buccolingual movement [9].…”
Section: Anesthetic Procedures and Tooth Extractionmentioning
confidence: 99%
“…Irradiation was performed immediately after tooth extraction and daily for 3 consecutive days more, corresponding to the dosage of 54 J/cm 2 per day (total dosage of 216 J/cm 2 which corresponds to 4 dosages), lasting 42 s on each application with close contact with the cervical region of the dental alveolus surface. These conditions had been determined by previous experiments [9,21]. The treatment protocol for the sham groups (control group) was the same as for the experimental group, except that the laser device was not switched on [21].…”
Section: Laser Devices and Laser Irradiation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation